Lymphocytotoxins in rheumatoid arthritis: prevalence, lymphocyte specificity, and HLA-DR antigens. Issue 2 (April 1981) - Wooley, P H; Panayi, G S; Batchelor, J R
Abstract : 37% (57/155) of sera from patients with rheumatoid arthritis contain cold-reacting lymphocytotoxic antibodies. Lymphocytotoxins were predominantly of the weakly reactive type and were more likely to be present in patients who were HLA-DR4 positive. By contrast, patients who were HLA-DR3 positive were more likely to have strongly reactive lymphocytotoxins. The lymphocyte subclass reactivity of the lymphocytotoxins was: 67% versus B lymphocytes, 27% against both T and B cells, and 7% for T cells.